Integrated braking force distribution for electric vehicle regenerative braking system - Ghazali, Anith Khairunnisa; Hassan, Mohd Khair; Mohd Radzi, Mohd Amran; As’arry, Azizan (Universiti Putra Malaysia, 2020)
The automotive industry has made a significant contribution to everyday life by fulfilling society’s mobility needs. Traditionally, electric vehicles (EV) were introduced as an alternative to the traditional internal combustion engine (ICE) to reduce the emission, which improves air quality. The regenerative braking system (RBS) technology is increasing rapidly as an alternative energy-saving solution instead of using the conventional fossil fuel process. In addition, conventional braking creates energy loss because it produces unnecessary heat during braking. Therefore, (RBS) was deliberately designed to solve these drawbacks. Several researchers have found an efficient way to recover regenerative energy, but do not pay enough attention to state-of-the-art (SOC), motor performance and overall performance. This paper designs a new braking force distribution that introduces integrated braking by combining the default ADVISOR and the new parallel braking distribution to improve the SOC battery for three driving cycles. The design of the braking part was based on the braking force distribution of vehicle speed, consisting mainly of friction and regenerative braking ratio allocation in parallel form. The suggested delivery method is evaluated by simulation and shows that the overall performance and battery life are increased. The proposed method was experimentally evaluated using ADVISOR Matlab for the efficiency and final state of the battery.